[Rezension von: Seamus, Taylor, Hate Crime Policy and Disability : From Vulnerability to Ableism] - Lynch, Kathleen (The British journal of criminology, 2024)
To the politically uninitiated, the task of introducing disability hate crime legislation might seem overwhelming. Through a careful and painstaking analys